Fintech and financial health in Vietnam during the COVID-19 pandemic: In-depth descriptive analysis - Robert Jeyakumar Nathan; Budi Setiawan; Mac Nhu Quynh (Journal of Risk and Financial Management, 2022)
The growing popularity of smartphones and the proliferation of technology have accelerated the development of the digital payment industry. Fintech enables customers to access financial services more efficiently and faster than traditional business, especially during the COVID-19 pandemic due to health protocols, including restrictions on physical contact. This study investigates financial literacy, fintech adoption, and the impact of the COVID-19 crisis on the financial health of consumers in Vietnam. The relatively higher level of the unbanked population in Vietnam and the lower level of adult financial literacy compared with the ASEAN region motivated this study. Based on judgment sampling, participants were approached using the mall intercept technique, and those familiar with fintech were selected for the research interview. Thirty participants were interviewed and were given a survey form to be filled online using their mobile phones. Data analysis was conducted using IBM SPSS software version 23. Perceived ease of use, perceived usefulness, trust, brand image, government support, user innovativeness, and attitude are found to be significantly correlated with fintech adoption in Vietnam, while financial literacy was found to be not significantly correlated with fintech adoption. Furthermore, further analysis using multiple linear regression revealed user innovativeness and attitude have a positive impact towards fintech adoption, and in contrast, financial literacy showed significant negative impact on fintech. This inverse relationship could indicate that in Vietnam, fintech may play a role of bringing financial inclusion where people with lower financial literacy are able to use technology for financial transactions, which was previously inaccessible to them. This could also mean that Vietnamese with higher financial literacy do not see fintech as an important tool for their financial transactions, as they may already have strong access to traditional financial facilities. This research contributes to knowledge in the field of Fintech adoption in Vietnam at the time of the COVID-19 outbreak. To foster greater financial inclusivity and access for the Vietnamese consumers, policy makers could promote the development of fintech business infrastructure and regulatory sandboxes to foster fintech startups.
Keywords: 330; fintech adoption; financial literacy; digitization in finance; financial inclusion; low income group; poverty alleviation; ASEAN